1999
DOI: 10.1161/01.hyp.33.6.1458
|View full text |Cite
|
Sign up to set email alerts
|

High Stress Responsivity Predicts Later Blood Pressure Only in Combination With Positive Family History and High Life Stress

Abstract: Abstract-High cardiovascular responsivity to stressors has not consistently improved prediction of later blood pressure increases beyond the predictive effects of baseline pressure. Animal models suggest that genetic susceptibility to hypertension and frequent stress exposure are important modulating factors in stress-related hypertension. Thus in 103 men originally tested at age 18 to 22 years and reassessed 10 years later, interactive effects of genetic susceptibility (defined as 1 or more hypertensive paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 37 publications
7
71
1
3
Order By: Relevance
“…9,10 One reason for these equivocal results is the fact that genetic factors are rarely accounted for in studies of BP reactivity. 11,12 A few studies have shown evidence for genes influencing BP changes in response to orthostasis (i.e., postural change), [13][14][15] but one aspect of this research that has been largely ignored is the identification of unique or shared genetic influences on different BP measures at rest and during orthostasis. In other words, do the same genes regulate BP both at rest and during orthostasis?…”
mentioning
confidence: 99%
“…9,10 One reason for these equivocal results is the fact that genetic factors are rarely accounted for in studies of BP reactivity. 11,12 A few studies have shown evidence for genes influencing BP changes in response to orthostasis (i.e., postural change), [13][14][15] but one aspect of this research that has been largely ignored is the identification of unique or shared genetic influences on different BP measures at rest and during orthostasis. In other words, do the same genes regulate BP both at rest and during orthostasis?…”
mentioning
confidence: 99%
“…The relationship between chronic stress and NK cytotoxicity has been well documented [15,33]. However, individuals vary in the degree of physiologic response to psychological stress [34][35]. Because this was an exploratory study, our goal was to examine only patients exhibiting a physiological response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, men with the combination of high stress responsivity and FH þ demonstrated higher blood pressure at a 10 year follow-up and a seven-fold increase in relative risk of change in blood pressure status compared to men without family history of hypertension (FHÀ) and low stress responsivity. 15 Regular exercise is associated with a lower incidence of hypertension, 16 although paradoxically, exercise may be viewed as potent stressor to the cardiovascular system. In FH þ the exercise pressor response appears to be exaggerated, 17,18 which is an independent predictor of future hypertension risk.…”
Section: Introductionmentioning
confidence: 99%